A proof-of-concept evaluation of a cloud-based store-and-forward telemedicine app for screening for oral diseases. (September 2016) - Estai, Mohamed; Kanagasingam, Yogesan; Xiao, Di; Vignarajan, Janardhan; Huang, Boyan; Kruger, Estie; Tennant, Marc
Objective: It is widely considered that telemedicine can make positive contributions to dental practice. This study aimed to evaluate a cloud-based telemedicine application for screening for oral diseases. Methods: A telemedicine system, based on a store-and-forward method, was developed to work as a platform for data storage. An Android application was developed to facilitate entering demographic details and capturing oral photos. As a proof-of-concept, six volunteers were enrolled in a trial to obtain oral images using smartphone cameras. Following an onsite oral examination, images of participants' teeth were obtained by a trained dental assistant. Oral images were directly uploaded from the smartphone to a cloud-based server via broadband network. The assessments of oral images by offsite dentists were compared with those carried out via face-to-face oral examinations. Results: A complete set of 30 oral images was obtained from all six participants. Out of 192 teeth reviewed, the proportion of ungradable teeth was 8%. Sensitivity and specificity of teledental screening were 57% and 100% respectively. The inter-grader agreement estimated for two examination modalities and between two teledental graders was 70% and 62% respectively. Findings indicate that the proposed system for screening of oral diseases can be implemented to provide a valid and reliable alternative to traditional oral screening. Conclusion: This study provided evidence that a robust system for store-and-forward screening for dental problems can be developed, and leads to the need for further testing of its robustness to confirm the accuracy and reliability of the teledentistry system.